No transfer of calibration between action and perception in learning a golf putting task - Van Lier, W.; Van der Kamp, J.; van der Zanden, A.; Savelsbergh, G. J. P. (Attention, Perception, & Psychophysics, 2011)
We assessed calibration of perception and action in the context of a golf putting task. Previous research has shown that right-handed novice golfers make rightward errors both in the perception of the perfect aiming line from the ball to the hole and in the putting action. Right-handed experts, however, produce accurate putting actions but tend to make leftward errors in perception. In two experiments, we examined whether these skill-related differences in directional error reflect transfer of calibration from action to perception. In the main experiment, three groups of right-handed novice participants followed a pretest, practice, posttest, retention test design. During the tests, directional error for the putting action and the perception of the perfect aiming line were determined. During practice, participants were provided only with verbal outcome feedback about directional error; one group trained perception and the second trained action, whereas the third group did not practice. Practice led to a relatively permanent annihilation of directional error, but these improvements in accuracy were specific to the trained task. Hence, no transfer of calibration occurred between perception and action. The findings are discussed within the two-visual-system model for perception and action, and implications for perceptual learning in action are raised.